2016
DOI: 10.1051/0004-6361/201527276
|View full text |Cite
|
Sign up to set email alerts
|

Three irradiated and bloated hot Jupiters:

Abstract: We report on three new transiting hot Jupiter planets, discovered from the WASP surveys, which we combine with radial velocities from OHP/SOPHIE and Euler/CORALIE and photometry from Euler and TRAPPIST. The planets WASP-76b, WASP-82b, and WASP-90b are all inflated, with radii of 1.7-1.8 R Jup . All three orbit hot stars, of type F5-F7, with orbits of 1.8-3.9 d, and all three stars have evolved, post-main-sequence radii (1.7-2.2 R ). Thus the three planets fit a known trend of hot Jupiters that receive high lev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 36 publications
7
76
2
1
Order By: Relevance
“…With a revised stellar radius of 1.969 ± 0.035 R (compared to 1.7 ± 0.03 R , Brown et al 2017), we find a ∼20% larger planetary radius of 2.078 +0.036 −0.044 R J (compared to 1.73 ± 0.03 R J ). As already suggested by Brown et al (2017), we find a larger impact parameter compared to that stated in the discovery paper (West et al 2016). A full list of the derived stellar and planetary parameters is given in Fig.…”
Section: Simultaneous Photometry With Eulercamsupporting
confidence: 83%
“…With a revised stellar radius of 1.969 ± 0.035 R (compared to 1.7 ± 0.03 R , Brown et al 2017), we find a ∼20% larger planetary radius of 2.078 +0.036 −0.044 R J (compared to 1.73 ± 0.03 R J ). As already suggested by Brown et al (2017), we find a larger impact parameter compared to that stated in the discovery paper (West et al 2016). A full list of the derived stellar and planetary parameters is given in Fig.…”
Section: Simultaneous Photometry With Eulercamsupporting
confidence: 83%
“…Our derived distances are listed in Table 4, available electronically from the CDS, and are generally within 2σ of the previously reported values. Notably different distances are those for WASP-66 and WASP-67, for which we find 520±30 pc and 184 ± 6 pc respectively, compared to 380 ± 100 and 255 ± 45 given by Hellier et al (2012); WASP-90, which we find to be at 211 ± 10 compared to 340 ± 60 by West et al (2016); and OGLE-TR-113, which we place at 358±19 pc, much closer than the previously reported distances of 600 pc by Konacki et al (2004) and 553 pc by Santos et al (2006).…”
Section: Host Star Distancescontrasting
confidence: 65%
“…We looked at the confirmed planets list from the NASA Exoplanet Archive 3 , and found that EPIC 229426032 b falls into a region of highly inflated hot Jupiters that is as yet not very well populated. We also compared the planet with other cases of highly inflated hot Jupiters, like WASP-17 b (Anderson et al 2010), WASP-82 b (West et al 2016), and WASP-12 b (Hebb et al 2009). These planets have shown to be good cases to perform atmospheric studies, which makes EPIC 229426032 b a good laboratory for studying the atmospheres of highly inflated planets as well.…”
Section: Discussionmentioning
confidence: 99%